Simplified Calculation of Maximum Wire Tension in case of Short Circuit - I. I. Sergey; A. P. Andrukevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Modified method for a simplified calculation of a maximum wire tension in case of a short circuit. This method makes it possible to take into account a real trajectory of their movement and elements of a switch-gear. An accuracy evaluation of the simplified calculation has been done with the help of a calculative experiment using a BusEf computer software. A correction factor has been obtained to take into account an influence of insulator strings on a tension value.